ChemInform Abstract: KF‐Loaded Mesoporous Mg—Fe Bi‐Metal Oxides: High Performance Transesterification Catalysts for Biodiesel Production. Issue 46 (24th October 2013) - Tao, Guiju; Hua, Zile; Gao, Zhe; Zhu, Yan; Zhu, Yan; Chen, Yu; Shu, Zhu; Zhang, Lingxia; Shi, Jianlin
Abstract A high performance transesterification catalyst, KF/Mg2Fe is synthesized by loading/dispersing KF in mesoporous Mg—Fe bi‐metal oxides with a Mg/Fe molar ratio of 2.